"AUTHOR'S SONG" OF THE PERIOD OF THE "REVOLUTION OF DIGNITY" AND THE WAR IN THE EAST OF UKRAINE - Сліпченко, Юлія (Ukrainian Cultural Studies, 2023)
The "author's songs" reflect the mood and emotions of Ukrainians during the "Revolution of Dignity" and the war in the East of Ukraine. These songs are important as a cultural phenomenon in the history of Ukraine, which demonstrates the feelings and thoughts of citizens through artistic expression. Moreover, they can serve as a source for understanding and analyzing the socio-political context of this period. On the other side, researchers can reveal the influence of these songs on society and the political process. The study of the author's songs can provide valuable conclusions about the role of art in developing civil society and various forms of struggle for freedom and justice that are especially important in the current context of national resistance. The purpose of the study is to analyze the Ukrainian "author's songs" of the period the "Revolution of Dignity" and the War in the East of Ukraine via their impact on the socio-political context. Systemic, semiotic, comparative, and comparative-typological methods were used in the research. Results. In the analyzed period of contemporary Ukrainian history, the "author's song" has provided support for the physical and moral mobilization of the Ukrainian people. Considering this, authors and performers of "author's songs" still maintain an important role in the cultural and political space. "Author's songs" reflect national traditions and cultural-historical memory, and provide the platform for the promotion of alternative public narratives to the authorities. Conclusions. "Author's songs" as a way to reflect reactions to the current socio-political context not only changed the perception of this genre for mass culture consumers but at the same time caused a significant impact on the national consciousness, provided a new attitude to the concept of nationalism and national self-identification. It was facilitated by the creativity of the bards, who created new ways of interacting with a disappointed society. This interaction got political significance due to the resonance of national sentiments and individual attitudes to the events of the authors-performers.
Keywords: "author's song"; bardic song; Revolution of Dignity; war; socio-political context